122k views
3 votes
2.) Fill in the blank.

csc^2 0 = cot ^2 0 + ___
A.) sec ^2 0
B.) -cos ^2 0
C.) -tan ^2 0
D.) 0
E.) 1

User Keyamoon
by
5.3k points

1 Answer

2 votes

Answer:

E.) 1

Explanation:

Firstly we will solve for L.H.S.

L.H.S. =
Csc^2\theta

Since we know that
Csc^2\theta is the inverse of
Sin^2\theta.

So we can say that;


csc^2\theta=(1)/(sin^2\theta)

Now For R.H.S.


Cot^2\theta+1

Since we can rewrite
cot^2\theta as
(cos^2\theta)/(sin^2\theta).

Now we can say that the R.H.S. is;


(cos^2\theta)/(sin^2\theta)+1

Now we add the fraction and get;


(cos^2\theta+sin^2\theta)/(sin^2\theta)

Now according to trigonometric identity;


cos^2\theta+sin^2\theta=1

So,
(cos^2\theta+sin^2\theta)/(sin^2\theta)=(1)/(sin^2\theta)

Here,


csc^2\theta=(1)/(sin^2\theta) and
Cot^2\theta+1 =
(1)/(sin^2\theta)

L.H.S. = R.H.S.

Hence
csc^2\theta=cot^2\theta+1

User Rugden
by
5.9k points